Radionuclide hepatic perfusion index and ultrasonography: assessment of portal hypertension in clinical practice - Seidlová, V; Hobza, J; Pumprla, J; Charouzek, J (Acta Universitatis Palackianae Olomucensis Facultatis Medicae, 1989)
The final value of portal blood flow pressure depends on the degree of vascular obstruction, then on the resistance in collateral vessels and, last, on splanchnic blood flow. The iniciating cause of portal hypertension most often lies in advancing anatomical damage leading to increased resistance and, consequently, to a reduction of portal blood flow, and simultaneous reciprocal development of extrahepatic collaterals. The determination of a true portal flow is a necessity particularly when deciding about a shunt surgery and its type, but it also supplies valuable information on the degree of portal flow restriction and, in this way, on the progress of pathophysiological changes, their extent and advance. The technique of radionuclide angiography and determination of the hepatic perfusion index (HPI) proposed by Sarper appears to be a profitable noninvasive method supplying well reproducible information on portal blood flow. Sarper proved it to be correlated with the degree of portal hypertension established by angiography. Ultrasonographic criteria of portal hypertension include dilatation of the portal vein in the region of the hilus hepatis exceeding 15 mm, and a more than 10 mm dilatation of the splenic vein above the spine. The mean HPI value obtained from the examination of 19 subjects without liver involvement was 0.6956 +/- 0.0583. The group of chronic hepatopathies included 19 patients with bioptically verified chronic hepatitis without reconstruction and/or steatosis, and 32 patients with liver cirrhosis likewise confirmed by biopsy: portosystemic shunts could be demonstrated in 14 of the latter. (ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: Hypertension, Portal; portální hypertenze; Radionuclide Angiography; Liver Cirrhosis; Collateral Circulation; ultrasonografie; vena portae; jaterní cirhóza; Hepatitis; lidé; Ultrasonography; Portal Vein; kolaterální oběh; Portal System; Liver Circulation; radioisotopová angiografie; hepatitida; jaterní oběh; portální systém; Humans